Chronic polystyrene microplastics exposure-induced changes in thick-shell mussel (Mytilus coruscus) metaorganism: A holistic perspective - Xing-Lu Chen; Lin-Jun Wu; Li-Li Miao; Lei Li; Long-Mei Qiu; Hui-Qiang Zhu; Xi-Rui Si; Hong-Fei Li; Qiao-Ling Zhao; Peng-Zhi Qi; Ting-Ting Hou (Ecotoxicology and Environmental Safety)
Microplastics have emerged as a significant global concern, particularly in marine ecosystems. While extensive research has focused on the toxicological effects of microplastics on marine animals and/or their associated microorganisms as two separate entities, the holistic perspective of the adaptability and fitness of a marine animal metaorganism—comprising the animal host and its microbiome—remains largely unexplored. In this study, mussel metaorganisms subjected chronic PS-MPs exposure experienced acute mortality but rapidly adapted. We investigated the response of innate immunity, digestive enzymes and their associated microbiomes to chronic PS-MPs exposure. We found that PS-MPs directly and indirectly interacted with the host and microbe within the exposure system. The adaptation was a joint effort between the physiological adjustments of mussel host and genetic adaptation of its microbiome. The mussel hosts exhibited increased antioxidant activity, denser gill filaments and increased immune cells, enhancing their innate immunity. Concurrently, the gill microbiome and the digestive gland microbiome respective selectively enriched for plastic-degrading bacteria and particulate organic matter-utilizing bacteria, facilitating the microbiome’s adaptation. The microbial adaptation to chronic PS-MPs exposure altered the ecological roles of mussel microbiome, as evidenced by alterations in microbial interactions and nutrient cycling functions. These findings provided new insights into the ecotoxicological impact of microplastics on marine organisms from a metaorganism perspective.